Prayer animal release: An understudied pathway for introduction of invasive aquatic species. Issue 4 (2nd October 2019) - Magellan, Kit
Abstract : It is more cost effective to prevent invasions than to eradicate or control invasive species once they are established. We therefore need a thorough knowledge of the pathways by which invasive species are introduced. Prayer animal release is the mainly Buddhist and Taoist tradition of releasing captive animals to gain merit. Although it is assumed to benefit the animals being released as well as the practitioners, prayer release as it is currently practiced has negative impacts that are at odds with the intended compassion. Major impacts are the introduction of invasive species and enhancement of spread and establishment. In this overview, I detail what is currently known about prayer release for aquatic invasions and provide consensus views of the best ways to address any potential impacts. Prayer release is rarely investigated as a potential pathway for introduction of invasive species and there is a marked lack of research on the subject, especially in aquatic ecosystems. Invasion researchers urgently need to 1) conduct research to establish the extent and impacts of prayer release, 2) engage with faith-based groups to encourage alteration of the practice so that it maintains its spiritual intent while promoting ecological responsibility, and 3) recognize prayer release as a major pathway for the introduction of invasive species.